SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEMPAT KOS UNTUK MAHASISWA DI LUWUK BANGGAI DENGAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) - Nurilmiyanti Wardhani; M. Adnan Nur (JTRISTE, 2017)
The purpose of this research is to design and implement a decision support system to selection of a boarding house using Simple Additive Weighting (SAW) method.Simple Additive Weighting method (SAW) is a method that can assist in decision making. However, using SAW as a weight method for decision support system only consider the biggest value among alternative choices . This method is only fit with the alternative choices that meets the specified criteria.The result shows that the decision support system built can help student in choosing boarding house. This system can also accelerate the decision making of student in choosing the boarding house.